Some results on (g, f)-uniform graphs - Gai, Jiansheng; Ge, Liansheng (Utilitas Mathematica, 2012)
A graph G is called a (g, f)-uniform graph if for each edge of G , there is a (g, f)-factor containing it and another (g, f)-factor excluding it. In this paper, some sufficient conditions for a graph to be a (g, f)-uniform graph are given and discussed.